Influence of Low-Level Red Laser Irradiation on the Proliferation, Viability, and Differentiation of Human Embryonic Stem Cell-Derived Mesenchymal Stem Cells - Khalid M. AlGhamdi; Ashok Kumar; Musaad Alfayez; Amer Mahmood (Life)
The present investigation was conducted to observe the effects of different energy densities of a low-level red laser (LLRL) on human embryonic stem cell-derived mesenchymal stem cells (hESC-MSCs). hESC-MSCs were cultured and irradiated with a LLRL from 0.5 to 5.0 J/cm2 at a wavelength of 635 nm. Biological parameters such as proliferation, viability, and migration were observed after 72 h of LLRL irradiation. Compared with the control, LLRL irradiation significantly increased the proliferation and viability of hESC-MSCs from 0.5 to 2.5 J/cm2 (p < 0.001, p < 0.05). LLRL irradiation from 0.5 to 3.0 J/cm2 significantly increased the migration of hESC-MSCs (p < 0.01). These results revealed that LLRL irradiation at lower energy densities significantly increased the proliferation, viability, and migration of hESC-MSCs. However, higher energy densities were ineffective; this was also true when we examined osteogenic differentiation, as low energy densities of LLRL had a positive effect on differentiation, whereas higher energy densities had a negative effect on alkaline phosphatase activity, Alizarin Red staining and gene expression analysis. In addition, not all stem cell markers were affected by the laser, and a slight decrease in the expression of CD146, which is a stemness marker, was detected, indicating improved differentiation. These findings indicate that low energy densities of LLRL irradiation have positive effects on the proliferation, migration, and differentiation of hESC-MSCs. However, higher energy densities showed inhibitory effects.